2021
DOI: 10.3389/fimmu.2020.593564
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Leptin in Modulating the Risk of Dermatological Diseases

Abstract: It is an indisputable fact that obesity is associated with a series of health problems. One important hallmark of obesity is excessive accumulation of lipids in the adipocyte, especially triglyceride (TG). Currently, the adipocyte has been considered not only as a huge repository of excess energy in the form of fat but also as an important source of multiple hormones and cytokines called adipokines. In obesity, the adipocyte is dysfunctional with excessive production and secretion of pro-inflammatory adipokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 95 publications
(111 reference statements)
1
12
0
Order By: Relevance
“…Moreover, a biologic may offer the most effective treatment for many people with moderate-to-severe psoriasis or psoriatic arthritis. These drugs target four different immune signalling pathways: (1) TNF-α inhibitors [116], such as adalimumab, certolizumab pegol, etanercept, infliximab and golimumab (2). IL-17 inhibitors, such as brodalumab, ixekizumab, and secukinumab.…”
Section: Psoriasis Treatment Considerations In Obese Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a biologic may offer the most effective treatment for many people with moderate-to-severe psoriasis or psoriatic arthritis. These drugs target four different immune signalling pathways: (1) TNF-α inhibitors [116], such as adalimumab, certolizumab pegol, etanercept, infliximab and golimumab (2). IL-17 inhibitors, such as brodalumab, ixekizumab, and secukinumab.…”
Section: Psoriasis Treatment Considerations In Obese Patientsmentioning
confidence: 99%
“…T helper cells, mast cells and neutrophils produce IL-17, which triggers the production of cytokines and chemokines in keratinocytes through an anticipant inflammatory response [ 39 ]. This process is accompanied by angiogenesis [ 2 , 121 ] and occurs at the level of the mainly visceral white adipose tissue that functions as an endocrine organ [ 40 ]. In psoriasis, the direct pathogenic cells are epidermal keratinocytes, inflammatory T cells, antigen-presenting cells, and dysregulation in the innate and adaptive immune system [ 33 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…We further showed that the drastic reduction in tumor growth induced by the combined sequential therapy was accompanied by a highly potent suppression of TME angiogenic capacity ( Figures 4 , 5 ; Table 4 ; Supplementary Figure S2 ). This was based on strong inhibitory actions (>90%) on VEGF (major angiogenesis coordinator), FasL (inducer of anticancer T-cell apoptosis at the vascular border), and leptin (stimulator of angiogenesis and overall accelerator of melanoma growth) ( Figures 4 , 5A ,C; Table 4 ) ( Apte et al, 2019 ; Su et al, 2020 ). In addition, the expression level of the CD31 marker of endothelial cell proliferation was also strongly inhibited ( Figures 5A,B ) and the macrophage density in melanoma tissue was significantly reduced in both IL-13-LCL-SIM and combination therapy groups, indicating an IL-13-LCL-SIM-mediated suppression of angiogenesis-promoting function of TAMs ( Figures 5A,D ).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin could accelerate the proliferation process in native CD4 + T cells and favored by reducing the levels of IFN from T cells [43,44]. During the wound healing process, leptin activates both inflammatory and proliferative phases in favor of tissue repair [45]. The increased plasma leptin level acts as an indicator of leptin-induced inflammatory response at the injury site.…”
Section: Leptin As An Immune Modulatormentioning
confidence: 99%